The development of shared values: Impact on employee behaviour and on customer perception of service - Adèle Thomas; Robyn Doak (South African Journal of Business Management, 2000)
Diversity of employees in the workforce is increasingly becoming a feature of South African business. Current debate in South Africa has concerned the marginalisation of groups of employees who, historically, have never been part of establishing existing corporate cultures, and accordingly, it has been argued that tensions exist in the workplace with a related negative impact upon company performance. The main aim of this exploratory study was to investigate whether the negotiated values system operating at a South African marketing and communications company impacts on decision making, cultural interaction and behaviour towards fellow employees and customers. A second aim of the study was to investigate whether the list of negotiated values at the company could be clustered into values categories for possible consideration by other organisations. The findings of the study appear to indicate that the negotiated values system positively impacts upon decision making in the company and upon employee behaviour both towards fellow employees and towards customers. The system also facilitates interaction and understanding amongst culturally diverse employees. It is also possible to cluster the values into four values categories that govern behaviour in different areas namely behavioural. interpersonal, developmental and team building values. It is concluded that the negotiated values system might be indicated as an effective tool for managing employee diversity in South African companies, both for the internal working together of employees and for the promotion of effective customer service.
Keywords: 650